PHARMACOGNOSTIC, ANTIOXIDANT AND ACUTE TOXICITY STUDY OF Ficus sycomorus (Linn) (Moraceae) ROOT AND STEM BARK - Namadina, Murtala M.; Haruna, H.; Sanusi, U. (FUDMA JOURNAL OF SCIENCES, 2020)
Most of biochemical reactions in the body generates Reactive Oxygen Species (ROS), which are involved in the pathogenesis of oxidative stress-related disorders like diabetes, nephrotoxicity, cancer, cardiovascular disorders, inflammation and neurological disorders when they attack biochemical molecules like proteins, lipids and nucleic acid. Antioxidants are used to protect the cells or tissues against potential attack by ROS. Most medicinal plants possess a rich source of antioxidants such as flavonoids, phenols, tannins, alkaloids among others. These phytochemicals are currently pursued as an alternative and complimentary drug. In this study, phytochemical components, antioxidant and acute toxicity study of the methanol extract of stem bark and root of F. sycomorus were carried out using standard methods. Findings from this study revealed the presence of some diagnostic microscopical features such as calcium oxalate, starch, gum/mucilage, lignin, Aleurone grain, suberized/Cuticular cell wall and inulin but calcium carbonate was absent in stem bark but present in the powdered root. Quantitative physical constants include moisture contents (6.40% and 7.82%), ash value (7.20% and 9.30 %) in stem bark and root respectively. Carbohydrates, alkaloid, flavonoids, saponins, tannins, glycoside, steroid, triterpenes and phenols were present in all the extracts. They were found to exhibit potent 1,1,-diphenyl 2-picryl hydrazyl (DPPH) free scavenging activity. The DPPH radical scavenging ability of the extracts showed the following trend Ascorbic acid < stem bark extractËƒ root extract. The LD50 of the methanolic stem bark and root extracts were found to be greater than 5000 mg /kg and is considered safe for use. Nonetheless, further